EFL students’ perceptions of ProWritingAid as an AI-powered writing support tool: A mixed-methods case study - Nada Aulia; Muarniati Muarniati; Fahul Ro'izki; Soni Ariawan (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
This research examines the utilisation of ProWritingAid, an AI-driven writing instrument, by English as a Foreign Language (EFL) students at Universitas Islam Negeri Mataram. The research employs a mixed-methods approach, with 104 participants from several institutions in Lombok, to assess the efficacy of ProWritingAid in enhancing writing skills, specifically in rectifying grammatical errors, improving sentence structure, and advancing vocabulary growth. The results indicate that 53.9% of students had significant vocabulary enhancement, whereas 39.4% noted increased writing confidence. Notwithstanding these favourable results, over 47% of participants expressed uncertainty regarding the tool's overall effect on their writing proficiency, indicating a need for additional investigation. Qualitative data obtained from interviews highlighted the tool's accessibility and user-friendliness, with students often comparing ProWritingAid to a personal writing instructor.Nevertheless, the report also underscores difficulties. Several students indicated challenges with the interface and articulated the necessity for enhanced training to effectively leverage the tool's functionalities. The findings indicate that ProWritingAid has considerable potential as an auxiliary educational tool within Technology-Enhanced Language Learning (TELL) frameworks, although its efficacy relies on user assistance and interface refinement.This research underscores the significance of incorporating technology-based tools into language instruction while tackling user problems. ProWritingAid can improve both academic and personal writing; nevertheless, maximising its advantages necessitates focused training and ongoing enhancements to the platform's usability. Such developments would reinforce its position as a transformative instrument for EFL learners in their pursuit of writing proficiency.